2018
DOI: 10.1186/s12969-018-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of tocilizumab to treat non-juvenile idiopathic arthritis in pediatric rheumatic patients: a literature review

Abstract: Tocilizumab, an anti-interleukin-6 (IL-6) agent, is indicated as a treatment for several autoimmune or inflammatory diseases, including rheumatoid arthritis and juvenile idiopathic arthritis (JIA). IL-6 plays roles in both immune system dysregulation and inflammation, and thus efforts to extend the utility of tocilizumab in patients with autoinflammatory conditions are ongoing. Here, we survey the literature on the off-label use of tocilizumab in patients with juvenile-onset rheumatic diseases including juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 83 publications
1
17
1
Order By: Relevance
“…All four patients had negative prick test but 3 of 4 had positive IDT. Tocilizumab has also been investigated in the off-label treatment of Takayasu arteritis in children and no ADR has been reported, while in other non-JIA rheumatic diseases some ADRs have been observed [58]. No HSR has been reported.…”
Section: Tocilizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…All four patients had negative prick test but 3 of 4 had positive IDT. Tocilizumab has also been investigated in the off-label treatment of Takayasu arteritis in children and no ADR has been reported, while in other non-JIA rheumatic diseases some ADRs have been observed [58]. No HSR has been reported.…”
Section: Tocilizumabmentioning
confidence: 99%
“…Chipps et al [65] and Rodrigo et al [66] found that anaphylaxis to omalizumab was rare. An incidence of 0.58% vs. placebo 1.04% (RR 0.51, p = 0.44) has been reported [58]. In the PROSE study [67] there were three anaphylaxes to omalizumab vs two for placebo and three for inhaled corticosteroids (ICS) boost.…”
Section: Omalizumabmentioning
confidence: 99%
“…Tocilizumab, intravenous (IV) or subcutaneous (SC) infusion, was the first drug approved by the Food and Drug Administration (FDA) respectively in 2010 and 2012, which resulted in rapid and sustained improvement in patients with RA. Tocilizumab was approved for use in children with polyarticular JIA as SC in 2013 [ 26 , 39 , 40 ].…”
Section: Interleukin-6mentioning
confidence: 99%
“…Tocilizumab or atlizumab (Actemra® or RoActemra®), is a humanized anti-IL-6 receptor mAb and binds to both soluble and membrane-bound IL-6 receptor. Its efficacy is currently being explored in the treatment of RA, systemic juvenile idiopathic arthritis in children, Castleman's disease, systemic lupus erythematosus (SLE), juvenile dermatomyositis (DM), vasculitis, and juvenile scleroderma [44]. Sarilumab (Kevzara®) is another human IgG1 mAb against IL-6 receptor developed for the treatment of RA [43].…”
Section: Anti-il-6 and Anti-il-6r Monoclonal Antibodiesmentioning
confidence: 99%